Malignant transformation of oral epithelial dysplasia – a registry-based study in the hospital district of Southwest Finland - Terävä, Antti; Nevanpää, Toni (My University, 2021)
Abstract Background. Oral epithelial dysplasia (OED) is considered a risk for oral squamous cell carcinoma (OSCC). A meta-analysis estimated a mean malignant transformation rate of 12.1% (95% CI 8.1–17.9). Methods. A total of 571 patients with diagnosis of OED were identified. Their potential subsequent diagnosis of OSCC was derived from the Finnish Cancer Registry. The risk of OSCC development in OED patients was compared with that of the general population without OED. Results. During a mean follow-up of 5.5 (range 0.1 – 29.0) years 10.9% of OED patients developed OSCC. OED patients had a 44.7 – fold risk (95% CI 34.4. – 56.7) for developing OSCC compared with the general population. The risk was at its highest within two years of OED diagnosis. Conclusion. OED patients in Southwest Finland have a significantly increased risk of developing OSCC relative to the general population, especially within the first two years of dysplasia diagnosis.